Success of uterine artery embolization in the management of postabortal arteriovenous malformations - Juneja, Sunil Kumar; Tandon, Pooja; Kaur, Gagandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Uterine artery arteriovenous malformations are an abnormal and non-functional connection between the uterine arteries and veins. It may be congenital or acquired. AVM can cause heavy menstrual bleeding and may have an impact on infertility. Uterine artery embolization is an alternate method to hysterectomy preserving the menstrual and reproductive function. Objectives of this study was to diagnose Arterio-venous malformations after abortions in patients with heavy menstrual bleeding and treating these patients with UAE. Methods: The retrospective study of patients with postabortal arteriovenous malformations managed at Dayanand Medical College and Hospital, during January 2012 to December 2018 was done. Inclusion criteria for this study post abortal heavy menstrual bleeding patients in reproductive age group diagnosed to be having AV malformations on CT angiography. Exclusion criteria for this study were H/O AUB prior to abortion, patients with fibroids, PID, endometriosis, adenomyosis, genital tract malignancies. Patients who do not have AV malformations on CT angiography. Results: This is a retrospective seven years study between January 2012 to December 2018 during which we received 23 patients who developed arterio-venous fistula following an abortion. The patients had heavy menstrual bleeding. All the patients had taken some hormonal treatment before reporting to us. All these patients underwent CT angiography. After that they all were subjected to UAE. All these patients were followed up to 6 months where they showed improvement in the symptoms. Conclusions: Acquired AVM is rare disorder following an abortion or a caesarean section. Heavy menstrual bleeding is a common symptom often requiring hysterectomy but with the advent of uterine artery embolization by blocking the uterine artery we can conserve the uterus where a lady can have normal menstrual and reproductive functions.